Efektivitas Mediasi dalam Penanganan Perceraian di Pengadilan Agama Ponorogo - Yulia Aswaty; Martha Eri Safira (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
Every civil case in court must be resolved through mediation first. As technology develops, PERMA No. 1 of 2016 concerning mediation provides an option for parties who cannot attend in-person to carry out audio-visual mediation. The purpose of this study was to find out how the implementation and effectiveness of direct and audio-visual mediation in the settlement of divorce cases in PA Ponorogo and what factors were supporting and inhibiting its effectiveness. This is an empirical study that employs a qualitative approach. data collection techniques use observation, interviews, and documentation, while the analysis uses inductive analysis. From this study, it was concluded that in divorce cases in PA Ponorogo, direct mediation was more effective than audio-visual. Factors supporting the effectiveness of direct mediation are the ability of a mediator and a reliable legal representative; the existence of legal awareness; the existence of good faith; and the existence of legal knowledge of the parties. Then there are the supporting factors of audio-visual mediation, which are adequate facilities, informative and educative communication of attorneys to their clients, good faith and legal knowledge of the parties, and the agreed schedule. While the inhibiting factors of the two mediation models are the panel of judges' policies, inadequate facilities, time zone differences, and the emotions of the parties.